Transcriptomic analysis of mouse TRAMP cell lines and tumors provide insights into shared pathways and therapeutic targets - Figueiredo, Marxa L.; Utturkar, Sagar; Kumar, Shreya; Fonseca-Alves, Carlos Eduardo [UNESP] (Elsevier, 2024)
The present study focused on comparing the gene expression profiles of different mouse models of prostate cancer, focusing on the TRAMP transgenic model and its derived cell lines and extending the comparisons to relevant genetically engineered mouse models and human prostate cancer datasets. Employing RNA sequencing, we examined different levels of prostate cancer aggressiveness from the original TRAMP cells to the TRAMP-C2 (TC2) derived cell line and extending to the aggressive TC2-Ras (TC2R) cells and tumors. TC2R acquire the ability to grow in bone tissue upon implantation, unlike the parental TC2 cells. Analysis identified upregulated genes in cell cycle regulation, immune response, and mitotic processes in TRAMP compared to wild-type tissues. TC2 cells exhibited unique gene profiles enriched in ECM organization and tissue development pathways, while TC2R cells showed increased cytokine signaling and motility genes, with decreased ECM and immune response pathways. In vivo TC2R models demonstrated enhanced ECM organization and receptor tyrosine kinase signaling in tumors, notably enriching immune processes and collagen degradation pathways in intratibial tumors. Comparative analysis among mouse and human datasets showed overlaps, particularly in pathways relating to mitotic cycle regulation, ECM organization, and immune interactions. A gene signature identified in TC2R tumors correlated with aggressive tumor behavior and poor survival in human datasets. Further immune cell landscape analysis of TC2R tumors revealed altered T cell subsets and macrophages, confirmed in single-cell RNA-seq from human samples. TC2R models thus hold significant promise in helping advance preclinical therapeutics, potentially contributing to improved prostate cancer patient outcomes.